2013
DOI: 10.3233/jem-130369
|View full text |Cite
|
Sign up to set email alerts
|

A methodological review of the Greek Annual Industrial Survey

Abstract: This paper is a comprehensive examination of the methodological evolution of the Annual Industrial Survey from its initiation in 1958 until 2010. Emphasis is given to the compliance of the survey with international methodological standards and to its conformity to relevant widely stipulated and accepted regulations. The existing literature using AIS data highlights its contribution to studies in several fields of economic research, going beyond those concerning the manufacturing sector, as well as to policy ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…According to the Foundation for Economic & Industrial Research (a private, non-profit, research organization in Greece), the percentage of the population aged 18-64 that is included in 2019 early stages of business activity, increased to 8.2% (approximately 536 thousand people) from 6.4% (418.000 people) in 2018. [2] Some other, results of the 2019 survey showed that almost 44% (from 37% in 2018) of start-up entrepreneurs started a new company in 2019 which operated for at least three months at the time of the survey (young entrepreneurs), with the rest -them aspiring entrepreneurs -still in the preparation phase. [2] Finally, 15.3% of early-stage entrepreneurs state that they will offer new and innovative products/services.…”
Section: Foundation For Economic and Industrial Research --Annual Ent...mentioning
confidence: 99%
See 4 more Smart Citations
“…According to the Foundation for Economic & Industrial Research (a private, non-profit, research organization in Greece), the percentage of the population aged 18-64 that is included in 2019 early stages of business activity, increased to 8.2% (approximately 536 thousand people) from 6.4% (418.000 people) in 2018. [2] Some other, results of the 2019 survey showed that almost 44% (from 37% in 2018) of start-up entrepreneurs started a new company in 2019 which operated for at least three months at the time of the survey (young entrepreneurs), with the rest -them aspiring entrepreneurs -still in the preparation phase. [2] Finally, 15.3% of early-stage entrepreneurs state that they will offer new and innovative products/services.…”
Section: Foundation For Economic and Industrial Research --Annual Ent...mentioning
confidence: 99%
“…[2] Some other, results of the 2019 survey showed that almost 44% (from 37% in 2018) of start-up entrepreneurs started a new company in 2019 which operated for at least three months at the time of the survey (young entrepreneurs), with the rest -them aspiring entrepreneurs -still in the preparation phase. [2] Finally, 15.3% of early-stage entrepreneurs state that they will offer new and innovative products/services. [2] These findings are a great example of how the entrepreneurial changes during the last years.…”
Section: Foundation For Economic and Industrial Research --Annual Ent...mentioning
confidence: 99%
See 3 more Smart Citations